GEOLOGI, MINERALOGI, DAN GEOKIMIA ENDAPAN BAUKSIT LATERIT DI DESA MUKTI JAYA, KABUPATEN SANGGAU, KALIMANTAN BARAT: GEOLOGY, MINERALOGICAL, AND GEOCHEMICAL LATERITE BAUXITE DEPOSITS IN MUKTI JAYA VILLAGE, SANGGAU DISTRICT, WEST KALIMANTAN - Permatasari, Aisha; Sabtanto Joko Suprapto; Priatna; Tatik Handayani; Dedi Sunjaya (Buletin Sumber Daya Geologi, 2024)
The geology of West Kalimantan, especially Sanggau Regency, contains a wide range of acidic to intermediate rocks of Lower Cretaceous age with stable tectonic conditions that meet the requirements for the formation of bauxite on an economical scale. The research area is in Mukti Jaya Village, Sanggau Regency, West Kalimantan Province. This research aims to determine the geology, mineralogical, and geochemical characteristics of bauxite deposits. The research methodology includes geological mapping, test pits, and laboratory analysis using XRF, A total of 390 bauxite samples were analyzed by XRF, 5 bauxite samples were analyzed by XRD, 4 bedrock samples and 2 bauxite samples were analyzed petrographically, and 2 bauxite concretion samples were analyzed mineragraphically. Based on the results of geological mapping, granodirite, quartz diorite and tonalite rocks were found. Bauxite is composed of the minerals quartz, gibbsite, kaolinite, hematite, biotite, boehmite, goethite, diaspor, muscovite, plagioclase, chlorite, and magnetite. From the results of XRF analysis content obtained 16.63% – 52.56% Al2O3; 14.5% – 66.69% TSiO2; 0.47% – 10.2% RSiO2; and 3.56% – 32.92% Fe2O3. The results of the correlation analysis showed a very strong and negatively correlated level of relationship between Al2O3 and TSiO2, as well as a very low level of relationship between Al2O3 and RSiO2. From the results of the regression analysis, it was found that TSiO2 had an effect on Al2O3 and RSiO2 had no effect on Al2O3.